2009
DOI: 10.1186/ar2736
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibody profiles in lupus nephritis with glomerular microthrombosis: a prospective study of 124 cases

Abstract: Introduction Glomerular microthrombosis (GMT) is a common vascular change in patients with lupus nephritis (LN). The mechanism underlying GMT is largely unknown. Although several studies have reported the association of antiphospholipid antibodies (aPL) with GMT, the relation between GMT and aPL remains controversial. Previous studies have demonstrated that some aPL could bind to several hemostatic and fibrinolytic proteases that share homologous enzymatic domains. Of the protease-reactive aPL, some can inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 51 publications
4
42
1
1
Order By: Relevance
“…In this retrospective study, the presence of GMT was 24.7%, which is consistent with previous studies . In addition, we also found that LN patients with GMT had more active and severe kidney disease than those without GMT, as evidenced by a higher SLEDIA, a higher activity index, more class IV LN, more active hematuria and proteinuria, and elevated levels of serum creatinine, which is also similar to the findings of previous studies …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this retrospective study, the presence of GMT was 24.7%, which is consistent with previous studies . In addition, we also found that LN patients with GMT had more active and severe kidney disease than those without GMT, as evidenced by a higher SLEDIA, a higher activity index, more class IV LN, more active hematuria and proteinuria, and elevated levels of serum creatinine, which is also similar to the findings of previous studies …”
Section: Discussionsupporting
confidence: 92%
“…GMT may be an important cause of renal injury and renal dysfunction in a subset of patients with LN, but the mechanisms underlying GMT in patients with LN remain obscure. To understand what factors confer the risk of GMT in LN, many previous studies examined the association of GMT with aPLs in patients with LN . However, the conclusions were highly controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several studies have suggested that IgA antib2 glycoprotein I (b2GPI) is the most prevalent isotype in SLE, with a significant association with thrombotic events [34] and an increased prevalence of morbidities involving organs of mucosal immunity [35]. Zheng et al [36] found that the lupus anticoagulant and antibodies against b2GPI and thrombin might play a role in glomerular microthrombosis. SLE patients with these factors had more severe renal tissue injuries and poorer renal function than those without them.…”
Section: Thrombotic Noninflammatory Vascular Lesionsmentioning
confidence: 99%